Athabasca River (Alice B. Donahue Library & Archives, 1930)
A view of the Athabasca River, possibly at Pelican Portage, Alberta. A note on the back reads: I lived in a log cabin 100 miles north of Athabasca for one winter (1929-30). The cabin was almost torn away by drifting ice in 1932. photograph